THE LIVER FUNCTION TEST (TRANSAMINASE ENZYMES AND BILIRUBIN) AND THE KIDNEY FUNCTION TESTS (UREA, CREATININE) ANALYSIS IN MDR-TB DURING TREATMENT - Widaninggar Rahma Putri; Havida Widyastuti; Dhini Intan Cahyani; Wa Ode Hikma Fajar (STIKes Mandala Waluya Kendari, 2026)
Background: Multi Drug Resistance Tuberculosis (MDR-TB) treatment caused side effects such as hepatotoxicity and acute kidney injury (AKI). Monitoring liver and kidney function in patients during treatment is crucial to prevent complication. Methods: A retrospective study of 19 patients confirmed MDR-TB in the period 2022-2025. Liver function test (transaminase enzymes and bilirubin) and kidney function test (urea and creatinine) during the first three month of treatment were analyzed. Results: Statistically, there was no difference in all parameters (p>0.05). Increases in total bilirubin, SGOT, SGPT levels occurred in the third month of TB treatment. While urea and creatinine levels increased in the second and third months. Conclusion: Monitoring of liver and kidney function during MDR-TB treatment is necessary to monitor patient condition.